2018
DOI: 10.1016/j.colsurfb.2018.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity on superhydrophobic titania nanotube arrays

Abstract: Bacterial infections are a serious issue for many implanted medical devices. Infections occur when bacteria colonize the surface of an implant and form a biofilm, a barrier which protects the bacterial colony from antibiotic treatments. Further, the anti-bacterial treatments must also be tailored to the specific bacteria that is causing the infection. The inherent protection of bacteria in the biofilm, differences in bacteria species (gram-positive vs. gram-negative), and the rise of antibiotic-resistant strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 46 publications
(83 reference statements)
3
48
0
Order By: Relevance
“…TiNTs have potential applications in several fields; they are found in biomaterials, gas sensors, adsorbents, heterogeneous catalysis ( photocatalysis, oxidation reactions, organic synthesis, biomass,…), biological activities to remove bacteria from water, solar cells, Li battery production, and many others. In particular, TiNTs have been used as a catalytic support for different active species (metals, oxides and sulfides).…”
Section: Introductionmentioning
confidence: 99%
“…TiNTs have potential applications in several fields; they are found in biomaterials, gas sensors, adsorbents, heterogeneous catalysis ( photocatalysis, oxidation reactions, organic synthesis, biomass,…), biological activities to remove bacteria from water, solar cells, Li battery production, and many others. In particular, TiNTs have been used as a catalytic support for different active species (metals, oxides and sulfides).…”
Section: Introductionmentioning
confidence: 99%
“…The S. aureus pellet was resuspended in NBM solution and an aliquot of P. aeruginosa was taken from the agar plate and dissolved in NBM. Both bacteria solutions were incubated at 37°C for 24 hr until the optical density at 600 nm was approximately 1 (Bartlet, Movafaghi, Dasi, Kota, & Popat, ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Bartlet et al indicated that one-dimensional titania nanotubes prepared by electrochemical anodization exhibit superhydrophobic behavior with a large water contact angle of >150°. Such superhydrophobic titania nanotubes reduced bacterial adhesion on their surfaces [82]. Reproduced with permission from [42].…”
Section: Crystal Structure Of Titaniamentioning
confidence: 99%